Benzotriazole removal on post-Cu CMP cleaning*Project supported by the Major National Science and Technology Special Projects (No. 2009ZX02308). (June 2015) - Tang, Jiying; Liu, Yuling; Sun, Ming; Fan, Shiyan; Li, Yan
Abstract This work investigates systematically the effect of FA/O II chelating agent and FA/O I surfactant in alkaline cleaning solutions on benzotriazole (BTA) removal during post-Cu CMP cleaning in GLSI under the condition of static etching. The best detergent formulation for BTA removal can be determined by optimization of the experiments of single factor and compound cleaning solution, which has been further confirmed experimentally by contact angle (CA) measurements. The resulting solution with the best formulation has been measured for the actual production line, and the results demonstrate that the obtained cleaning solution can effectively and efficiently remove BTA, CuO and abrasive SiO2 without basically causing interfacial corrosion. This work demonstrates the possibility of developing a simple, low-cost and environmentally-friendly cleaning solution to effectively solve the issues of BTA removal on post-Cu CMP cleaning in a multi-layered copper wafer.